INTEGRASI KEUANGAN DAN DATA PEMASARAN DIGITAL GUNA EFISIENSI UMKM DESA SUMBUNG - Amy Wulandari; Rosita; Heri Susanto; Ida Ayu Kade Rachmawati Kusasih; Lintang Kurniawati; Nur Asih Triatmaja; Hari Purwanto (KRIDA CENDEKIA, 2025)
This study describes an MSMEs assistance program implemented in Sumbung Village, focusing on enhancing digital capabilities through spreadsheet based financial system training and social media marketing strategies. A mixed-methods approach was employed, combining qualitative and quantitative analyses conducted over a defined period to evaluate the program’s impact on participating MSMEs. The results indicate significant improvements in financial management efficiency and digital marketing reach. The adoption of digital financial record keeping notably reduced administrative workload and improved reporting accuracy. In terms of marketing, creative content training effectively expanded audience reach and contributed to increased sales growth. Statistical analyses confirmed significant differences in all performance indicators before and after the intervention. Challenges faced during implementation included limited digital infrastructure and varying levels of technological readiness among participants. These findings highlight the importance of continuous mentoring and context specific approaches that consider the unique characteristics of rural MSMEs. This program serves as a relevant model for developing technology driven MSMEs empowerment policies in similar contexts. Recommendations include strengthening the supporting ecosystem and fostering peer learning communities for local business owners